P-Hacking: A Wake-Up Call for the Scientific Community. - Raj, A. Thirumal; Patil, Shankargouda; Sarode, Sachin; Salameh, Ziad (Science & Engineering Ethics, 2018)
P-hacking or data dredging involves manipulation of the research data in order to obtain a statistically significant result. The reasons behind P-hacking and the consequences of the same are discussed in the present manuscript.